Dekonstruksi sistem patriarki dan pencarian identitas novelis perempuan Indonesia tahun 2000-an - Wiyatmi, Wiyatmi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
This article is intended to understand the phenomenon of women writers in Indonesian literature in the 2000s. Their literary works emerged amid a literary field dominated by male writers. Viewed from a feminist perspective, these women writers strive to assert their position by attempting to deconstruct the patriarchal system. Through their works, they seek identity through literary production and literary criticism. Their existence in Indonesian literature in the 2000s became a pioneering form of women’s rebellious action against the patriarchal system in Indonesian literary history. Through works that received awards from Dewan Kesenian Jakarta and the Khatulistiwa Literary Award, their writing capabilities have been recognized. However, their skill in producing literary works does not necessarily receive positive responses from either society or literary critics. Many harsh criticisms attempt to marginalize their works.